Compliance, toxicity and efficacy in weekly versus 3-weekly cisplatin concurrent chemoradiation in locally advanced head and neck cancer. Issue 1 (4th September 2018) - Muzumder, Sandeep; Srikantia, Nirmala; Vashishta, Ganesha Dev; Udayashankar, Avinash H.; Raj, John Michael; Sebastian, M. G. John; Kainthaje, Prashanth Bhat
Abstract: Aim: Weekly low-dose cisplatin is routinely used in concurrent chemoradiation (CCRT) in locally advanced head and neck cancer (LAHNC), despite 3-weekly cisplatin being the standard of care. We compared compliance, toxicity and efficacy in weekly versus 3-weekly cisplatin CCRT in LAHNC. Materials and methods: In this retrospective study, weekly cisplatin 50 mg flat dose was compared with 3-weekly cisplatin 100 mg/m 2, when given in CCRT in LAHNC with curative intent. The study outcome was compliance, toxicity, loco-regional control (LRC), disease-free survival (DFS) and overall survival (OS). Results: Eighty-four patients received CCRT from January 2013 to June 2017, 40 in weekly and 44 in 3-weekly arm. There was no difference between the arms not completing scheduled radiation therapy or chemotherapy. Patient receiving 200 mg/m 2 cisplatin is higher in 3-weekly arm compared with weekly arm (75 versus 40·9%; p <0·0015). Compared with 3-weekly arm, more patient in weekly arm developed grade ≥3 mucositis (52·5 versus 15·9%, p =0·0004), day care intravenous hydration (82·5 versus 38·6% <0·0001) and in-patient admission (55·0 versus 18·2%; p =0·0004). The 2-year LRC, DFS and OS in weekly versus 3-weekly arm were: 70 versus 61·4% ( p =0·406); 67·5 versus 56·8% ( p =0·314); 67·5 versus 61·4% ( p =0·558), respectively. The median time to LRR, DFs and OS was not reached. Conclusions: Weekly cisplatin is comparable with 3-weekly cisplatin in terms of compliance, disease control and survival, but with increased grade 3 mucositis and higher admissions for supportive care.